2003
DOI: 10.1227/01.neu.0000053152.45258.74
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Image Transfer System through a Mobile Telephone in Japan: Technical Note

Abstract: The mobile phone system is adequately useful for early diagnosis and initiation of treatment in emergent cases. This is attributable to its low cost and ease of handling for sending images to remote areas and between hospitals, despite the small dimensions of the monitor. Better-quality image transfer will be realized through an advanced mobile phone system based on the new International Mobile Telecommunication 2000 standards, which also will be useful in the development of telemedicine and telecare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 5 publications
0
55
0
4
Order By: Relevance
“…Many direct-screen photographing methods using PDAs with either an external or a built-in digital camera that enables direct digital capturing of the PC screen have been researched. 5,6 They can achieve timely transmission with easy operation, but the image distortion occurring during the capturing process compromises the high-quality display necessary for radiological images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many direct-screen photographing methods using PDAs with either an external or a built-in digital camera that enables direct digital capturing of the PC screen have been researched. 5,6 They can achieve timely transmission with easy operation, but the image distortion occurring during the capturing process compromises the high-quality display necessary for radiological images.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to this method is to photograph the PACS monitor using a digital camera, which allows the user to bypass the menu navigation system. 5,6 Because most PDA phones have a built-in digital camera, the use of a PDA phone can be convenient to perform both the photographing and transmitting processes and can also avoid a synchronization problem. However, some distortions occurring during the photographing process cannot be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Jayesh Modi, Pranshu Sharma, Alex Earl, Mark Simpson, J. Ross Mitchell, Mayank Goyal have been addressed by many investigator [1][2][3]12,13 . However, patient confidentiality, especially when medical information is downloaded on a portable device, remains a significant concern.…”
Section: Iphone-based Teleradiology For the Diagnosis Of Acute Cervicmentioning
confidence: 99%
“…
An instant image transfer system can be used to support rapid medical and imaging decision making in an emergency situations when doctors are away from the hospital [1][2][3] . There are several Web-based picture archiving and communication systems, which allows access to a patient's radiological images from outside the hospital 1 .
…”
mentioning
confidence: 99%
“…Previous studies have shown the potential for evaluating emergent imaging findings with mobile devices [6][7][8][9]. Early studies evaluated personal computers for diagnosing imaging findings before mobile devices were technologically sufficient to view radiological images [10].…”
Section: Introductionmentioning
confidence: 99%